Literature Riview: Analisis Tingkat Pengetahuan dan Kesiapsiagaan Masyarakat Dalam Menghadapi Bencana Alam - Arfan Zidni Maulana; Nielsa Sastya; Abdurrozzaq Hasibuan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Several journals discuss the relationship between knowledge and preparedness in facing natural disasters such as landslides, earthquakes, floods and volcanic eruptions. These studies involve communities, students and villages in various regions in Indonesia. Disaster management laws are also mentioned in several journals. This literature study discusses the level of knowledge and preparedness of society in facing natural disasters such as earthquakes and floods. The research results show that the training and outreach program is effective in increasing community knowledge and preparedness. It is important to raise awareness and conduct training programs to build resilient communities in disaster-prone areas. Community knowledge and preparedness in facing natural disasters is very important to reduce disaster risk. Various studies show that the level of community knowledge and preparedness can influence the effectiveness of responses to disasters. The research method used to study this is survey and retrospective observational techniques. The research results show that people who have a good level of knowledge and preparedness tend to be better prepared to face natural disasters.